Inside Cover: Ethynyl‐Linked Donor‐π‐Acceptor Boron Dipyrromethenes for Panchromatic Dye‐Sensitized Solar Cells (Asian J. Org. Chem. 6/2017). Issue 6 (1st June 2017) - Shi, Wen‐Jing; Kinoshita, Takumi; Ng, Dennis K. P.
Abstract : Boron dipyrromethenes (BODIPYs) are versatile functional dyes that have found widespread applications. By introducing a triarylamino electron donor and a 4‐carboxyphenyl electron acceptor/anchoring group (with or without a benzothiadiazole bridge) to the opposite C2 and C6 positions of a BODIPY core via an ethynyl linker, the resulting conjugates could exhibit panchromatic absorptions in the UV/Vis region and serve as efficient photosensitizers for dye‐sensitized solar cells with a photovoltaic conversion efficiency of up to 3.41%. More information can be found in the Full Paper by Wen‐Jing Shi, Takumi Kinoshita, and Dennis K. P. Ng onpage 758 in Issue 6, 2017 (DOI:10.1002/ajoc.201700121 ).